Inflation Stability and Economic Recovery Through Monetary Policy Instruments in Indonesia - Pipit Yuspira; Wahyu Indah Sari; Rusiadi Rusiadi (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the role of monetary policy in maintaining inflation stability and supporting economic recovery in Indonesia. Specifically, this study examines the simultaneous relationship between interest rates, money supply, and Gross Domestic Product (GDP) on inflation, as well as the effects of the exchange rate, unemployment rate, and inflation on GDP. The research approach used is quantitative with the simultaneous equation system analysis method. The data used are secondary time series data from Indonesia for the period 20102024. Model estimation was performed using the Two-Stage Least Squares (2SLS) method to address potential endogeneity between variables. The results show that interest rates partially have a negative and significant effect on inflation, while money supply and GDP have an effect but are not significant on inflation. In the second equation, the exchange rate and unemployment have a negative effect on GDP, while inflation has a positive effect, but all are statistically insignificant. The results of normality and autocorrelation tests indicate that the model meets classical assumptions and is suitable for use. Overall, the findings of this study indicate that monetary policy instruments, particularly interest rates, have an important role in controlling inflation, but their impact on economic growth is still limited during the study period. Therefore, coordination between monetary and other policies is necessary to maintain economic stability while promoting sustainable economic growth.